Java network programming - Harold, Elliotte Rusty (O'Reilly, 2005)
The new third edition of this highly regarded introduction to Java networking programming has been thoroughly revised to cover all of the 100+ significant updates to Java Developers Kit (JDK) 1.5. It is a clear, complete introduction to developing network programs (both applets and applications) using Java, covering everything from networking fundamentals to remote method invocation (RMI). Java Network Programming, 3rd Edition includes chapters on TCP and UDP sockets, multicasting protocol and content handlers, servlets, multithreaded network programming, I/O, HTML parsing and display, the Jav.